Intercultural paradigms of educational self-management action - Barrera, Martha Lucia Izquierdo (Universidad Autónoma Indígena de México, 2018)
he purpose of this paper is to tell the experience of the BA in ethno education and community development of the Universidad Tecnologica de Pereira, Colombia, with indigenous communities “Embera Chamí” in the departments of Caldas and Risaralda, here in Colombia. We begin with a sociohistorical and conceptual tour with the indigenous education emergence in order to contextualize to the readers which scope we are going to work in. the second part is a tour of the institutional context _sciences for the education faculty at Universidad Tecnologica de Pereira and the creation of the BA in ethno education and community development.For finishing telling the intercultural education process from the community education.